The clinimetric properties of aerobic and anaerobic fitness measures in adults with cerebral palsy: A systematic review of the literature. (October 2015) - Lennon, Nancy; Thorpe, Deborah; Balemans, Astrid C.; Fragala-Pinkham, Maria; O'Neil, Margaret; Bjornson, Kristie; Boyd, Roslyn; Dallmeijer, Annet J.
Highlights: Evidence is emerging for good feasibility, validity, and reliability of lab-based aerobic and anaerobic bicycle tests in adults with CP who are ambulatory or partially ambulatory. Bicycle ergometry tests should be considered as potential outcome measures for exercise intervention studies for ambulatory or partially ambulatory adults with CP. No valid or reliable fitness capacity measurement protocols for adults with CP who have moderate to severe mobility restrictions were identified. No valid or reliable field-based fitness capacity tests for adults with CP of any functional ability were identified. Abstract: Objective: To analyze the clinimetric properties of maximal aerobic and anaerobic fitness measurement protocols in adults with cerebral palsy (CP). Data Sources: A systematic search through March 2015 of databases PubMed, Embase, SPORTDiscus and PsycINFO was performed with medical subject heading terms for 'cerebral palsy' combined with search terms adults or adolescents and multiple text words for fitness and exercise tests that yielded 864 articles. Study Selection: Abstracts were screened by two reviewers to identify use of maximal fitness measurements in adolescents (14–18 yrs) or adults (>18 yrs) with CP of all abilities. Ninety-four articles were reviewed. No studies of adolescent (14–18 yrs) qualified. Eight articles reported clinimetric properties for adults with CP who walk or propel a wheelchair independently. Five articles reported on aerobic capacity, one reported on anaerobic capacity and two reported on both. Data Extraction: Methodological quality of the studies was rated using portions of the COSMIN (COnsensus-based Standards for the selection of health status Measurement INstruments) checklist. Quality of the measurement protocols was evaluated based on statistical strength of the clinimetrics. Synthesis of the overall evidence was based on the Cochrane review group guidelines which combine methodological quality and statistical strength. Data Synthesis: Eight articles reported on 4 aerobic and 1 anaerobic protocols. Overall synthesis revealed that for ambulatory adults with CP there is (i) moderate evidence for good reliability and good construct validity of maximal aerobic and anaerobic cycle tests, (ii) moderate evidence for good criterion validity of sub-maximal aerobic cycle tests, and (iii) strong evidence for poor criterion validity of the six-minute walk test as a maximal aerobic test. And for adults who propel a wheelchair there is limited evidence of good reliability for maximal aerobic wheelchair ergometer tests. Conclusions: Limited quality research exists on the clinimetric properties of aerobic and anaerobic capacity measures for adults with CP who have independent mobility. Quality aerobic and anaerobic measures for adults with more severe mobility impairments are absent.